2022
DOI: 10.3390/dj10040064
|View full text |Cite
|
Sign up to set email alerts
|

Molar Incisor Hypomineralization: Awareness among Postdoctoral Dental Residents: A Cross-Sectional Study

Abstract: Background: Molar incisor hypomineralization (MIH) is the presentation of an enamel defect, where incisors and one (or more) molars are affected. Identifying MIH is significant in restoring its visual defect and avoiding pain or other consequences of this condition. The present cross-sectional study aimed to evaluate the awareness, ability, and confidence in identifying MIH among postgraduate residents in the state of Nevada. Methods: This cross-sectional study was conducted among postdoctoral dental residents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…With regard to this study’s results, all of our students stated that they had difficulty in distinguishing MIH from other dental anomalies, as in similar studies [ 18 , 31 ]. In a study conducted at the University of Nevada School of Dentistry in Las Vegas [ 18 ], postdoctoral dentists reported that they most often confused it with fluorosis, followed by amelogenesis imperfecta, whereas in a similar study in Syria [ 31 ], senior dental students reported that they had the most difficulty distinguishing it from amelogenesis imperfecta and enamel hypoplasia. In our study, the 4 th -year students stated that they confused it with amelogenesis imperfecta and enamel hypoplasia and the 5 th -year students confused it with enamel hypoplasia and amelogenesis imperfecta, respectively.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…With regard to this study’s results, all of our students stated that they had difficulty in distinguishing MIH from other dental anomalies, as in similar studies [ 18 , 31 ]. In a study conducted at the University of Nevada School of Dentistry in Las Vegas [ 18 ], postdoctoral dentists reported that they most often confused it with fluorosis, followed by amelogenesis imperfecta, whereas in a similar study in Syria [ 31 ], senior dental students reported that they had the most difficulty distinguishing it from amelogenesis imperfecta and enamel hypoplasia. In our study, the 4 th -year students stated that they confused it with amelogenesis imperfecta and enamel hypoplasia and the 5 th -year students confused it with enamel hypoplasia and amelogenesis imperfecta, respectively.…”
Section: Discussionsupporting
confidence: 69%
“…This, in turn, leads to poor retentive etching patterns and higher failure rates in adhesive fillings, which, among other factors, makes clinical management of MIH-affected teeth regarding cavity design and material choices a serious issue [ 17 ]. As it is a difficult condition for clinicians to manage, it is crucial for clinicians to develop awareness, identification skills, and knowledge of its treatment to provide efficient and high-quality oral health care to those affected [ 18 ].…”
Section: Introductionmentioning
confidence: 99%